2019
DOI: 10.1186/s12913-019-4110-5
|View full text |Cite
|
Sign up to set email alerts
|

Peer support interventions for individuals with acquired brain injury, cerebral palsy, and spina bifida: a systematic review

Abstract: Background Neurological disorders may negatively impact community integration and/or quality of life. Peer support has emerged as a potential strategy to enhance patients’ efficacy in managing their own health. This review examines the key characteristics and impact of peer support interventions for adults with acquired brain injury, cerebral palsy, and spina bifida on community integration and quality of life. Methods Eligible studies reported on peer support intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
2
22
1
Order By: Relevance
“…Our research team has previously conducted a systematic review examining the impact of peer support interventions for individuals with acquired brain injury, cerebral palsy, and spina bifida. We identified that logistical challenges (e.g., geographical distance and scheduling difficulties) act as barriers to participation in peer support programs, but are mitigated by facilitators such as a common background and/or sense of identity between mentors and partners [ 12 ]. Furthermore, previous studies in other disease populations have identified barriers and facilitators to participation in peer support programs that overlap with many of the themes that emerged in the current study [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research team has previously conducted a systematic review examining the impact of peer support interventions for individuals with acquired brain injury, cerebral palsy, and spina bifida. We identified that logistical challenges (e.g., geographical distance and scheduling difficulties) act as barriers to participation in peer support programs, but are mitigated by facilitators such as a common background and/or sense of identity between mentors and partners [ 12 ]. Furthermore, previous studies in other disease populations have identified barriers and facilitators to participation in peer support programs that overlap with many of the themes that emerged in the current study [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews of peer support interventions for brain injury have examined peer support for the rehabilitation of individuals with acquired brain injury [23]; one-to-one peer mentoring for people with TBI [4], and; peer support groups following acquired brain injury [25]. However, the effects of peer support for individuals with TBI have only been studied in two other RCTs [24]: a 2012 study by Hanks et al [50] which included peer mentoring for individuals with TBI (n = 96) and their caregivers or significant others (n = 62), and a 2011 study by Struchen et al [51] which examined a social peer mentoring program for individuals with TBI (n = 30).…”
Section: Similarity Of Results From the Obia Peer Support Program To Previous Studiesmentioning
confidence: 99%
“…However, many of these studies discuss the need for further research on the adaptation of interventions to the needs of individuals, populations, and settings, as well as the optimal implementation of specific intervention components and sustainability of intervention outcomes. Recent systematic reviews which have been conducted on peer support for individuals with brain injury have focused on acquired brain injury, one-to-one peer mentoring, and peer support groups, with further investigation of specific intervention characteristics such as dosage, length, and communication type recommended [4,[23][24][25]. A systematic review conducted by members of our research team showed a notable absence of underlying theories supporting the majority of interventions [24].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to characterise individual differences that can have a mediating effect on treatment success, we will evaluate cognitive functions, differences in the processing and integration of music, music reward, perseverance and social support at the beginning of the intervention. Therefore, the baseline evaluation will include the Spanish version of the Montreal Cognitive Assessment [ 45 , 62 ] to assess global cognitive function, the digit span (included in the Wechsler Adult Intelligence Scale, WAIS-IV, [ 97 ]; adapted to Spanish by Pearson Clinical & Talent Assessment) to assess working memory, a short version of the Boston Naming Test validated in Spanish [ 14 , 47 ] to assess language production, and the vocabulary subtest of the WAIS-IV. In addition, the scale and rhythm subtests from the shortened version of the Montreal Battery of Evaluation of Amusia [ 68 ] will be used to screen for amusia at baseline.…”
Section: Methodsmentioning
confidence: 99%